2018
DOI: 10.3390/pathogens7030060
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Response to Propionate Is Differentially Modulated by Anaerobicity

Abstract: Propionate is a common food preservative and one of the major fermentation acids in the intestines. Therefore, exposure to propionate is frequent for foodborne pathogens and likely takes place under suboxic conditions. However, it is not clear whether the absence of oxygen affects how pathogens respond to propionate. Here, we investigated how propionate exposure affects Listeria monocytogenes growth and virulence factor production under aerobic or anaerobic conditions and showed that oxygen indeed plays a key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Both propionate and butyrate, separately, have been demonstrated to decrease the abundance of branched chain fatty acids (BCFAs) and increase the abundance of straight chain fatty acids in L. monocytogenes [8,9]. Here we investigated how the membrane fatty acid composition was affected by supplementation of SCFAs in mixtures and whether there was an oxygen-dependent alteration of fatty acid composition in response to SCFA exposure.…”
Section: Scfa Supplementations Altered Membrane Fatty Acid Compositionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both propionate and butyrate, separately, have been demonstrated to decrease the abundance of branched chain fatty acids (BCFAs) and increase the abundance of straight chain fatty acids in L. monocytogenes [8,9]. Here we investigated how the membrane fatty acid composition was affected by supplementation of SCFAs in mixtures and whether there was an oxygen-dependent alteration of fatty acid composition in response to SCFA exposure.…”
Section: Scfa Supplementations Altered Membrane Fatty Acid Compositionsmentioning
confidence: 99%
“…In a subsequent study investigating the effects of propionate on L. monocytogenes under aerobic as well as anaerobic conditions identified that the production of LLO was highly sensitive to regulation by exogenous propionate [9]. More specifically, while aerobic propionate exposure resulted in a dose-dependent decrease in LLO production, anaerobic propionate exposure resulted in a dose-dependent increase in LLO production [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations